PENGARUH PEMBERIAN GEL AIR KELAPA GADING (COCOS CAPITATA) TERHADAP TINGKAT KECEMASAN PADA HIPERSENSITIVITAS DENTIN Studi in vivo terhadap tikus wistar jantan - Chariza Hanum Mayvita Iskandar; Yayun Siti Rochmah; Arlina Nurhapsari (ODONTO : Dental Journal, 2016)
Background: Ivory palm water (Cocos capitata) has a high potassium content. Potassium ion can depolarized excited dental nerve on dentin hypersensitivity. This study was to determine the effect of water gel ivory palm against dentine hypersensitivity by the anxiety level of mice using RGS (Rat Grimace Scale).Method: This research has been through ethical clearance which researchmethod was quasy experimental in vivo. The sample was 16 Wistar rats (Rattus novergicus) male 4-5 months with 4 mice in each group. Group I as a positive control. Group II as the ivory palm water gel 10% treatment group. Group III as the ivory palm water gel 70% treatment group. Group IV as a negative control. Research data analysis used Kruskal Wallis test with p <0.05 then continued by Mann Whitney test.Result: Kruskal Wallis test obtained significant difference between the four study groups (p <0.05). Mann Whitney test results in comparison either between positive control group and ivory palm water gel 10% and 70%, and comparison group of ivory palm water gel 10% and 70% weren’t significantly different.Conclusion: This study conclusion there was no significant difference between ivory palm water gel 10 % and 70 % in reducing anxiety level in male Wistar rats with dentinal hypersensitivity